Analisis Pengaruh Gempa Dan Tsunami Di Jepang terhadap Saham-Saham Perusahaan Di Bursa Efek Indonesia - , Anti Anggraini ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This study is an empirical research to analyze whether there is negative abnormal return as a result of natural disaster events. In this case, the event of natural disaster is Japanâs earthquake and tsunami that occurred on March 11, 2011. The data used in this study are daily closing stock prices and daily market indices (JKSE). This research using a purposive sampling method with criterias as follow: (1) Stock has complete data of stock price movements, (2) Registered during the period of observation period, (3) The stock was not doing dividend announcement, stock split, and right issue. The sample used in this study is 32 sample stocks in Indonesia Stock Exchange. Market model is used to calculate the expected return. The analysis shows that there is market reaction, but it does not increase the wealth of investors because the abnormal returns that occur are not significant.